Karakteristik Pupuk Organik Cair Berbasis Limbah Vinasse Melalui Teknologi Aktivasi : Characteristics Of Vinasse Waste-Based Liquid Organic Fertilizer Through Activation Technology - Angga Handika Putra; Wanti Mindari; Purwadi Purwadi (Agrocentrum, 2023)
Utilization of vinasse waste as POC has great potential in the agricultural sector. This is because there is an abundance of vinasse waste originating from the bioethanol industry sector. So action is needed so that vinasse waste can be utilized into a profitable product. This research aims to test the potential of vinasse waste if it is processed into POC. Apart from using vinasse waste as the main raw material, the formula also added organic ingredients such as straw ash, humate, husk charcoal and filter cake dregs which were fermented for 5 weeks. Based on the research results, the content of N, P, K and C-organic elements cannot comply with the 2019 Ministry of Agriculture Quality Standards. Meanwhile, the content of Na and pH elements is appropriate, but for Fe only the F2 and F4 T1 treatments can be appropriate.